2010
DOI: 10.3109/09513590.2010.493248
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation ofUGT1A1andSULT1A1polymorphisms with lipid levels in women with different hormonal status

Abstract: The data showed the presence of an association between the UGT1A1*28/*28 and SULT1A1*2/*2 and T-chol and LDL-C levels in women with different hormonal status. No previous studies investigated the association of the polymorphisms examined in this study with lipoprotein levels in women separately by hormonal status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…These data fail to support data presented by Tapan et al [56] who showed reduced sd-LDL in a cohort of male, age and BMI matched individuals, indicating the possibility of gender dependent perturbation of cholesterol homeostasis in GS. Such conclusions are further supported by the elegant experiments of Smiderle et al [57], who showed premenopausal women possessing the 7/7 TA repeat polymorphism had significantly reduced TC concentrations, versus individuals with the 6/7 or 6/6 polymorphism. The 7/7 TA repeat polymorphism is associated with hyperbilirubinemia [58], however, bilirubin concentrations were not reported in this study.…”
Section: Bilirubin and Lipid Status 141 Gilbert's Syndromementioning
confidence: 71%
“…These data fail to support data presented by Tapan et al [56] who showed reduced sd-LDL in a cohort of male, age and BMI matched individuals, indicating the possibility of gender dependent perturbation of cholesterol homeostasis in GS. Such conclusions are further supported by the elegant experiments of Smiderle et al [57], who showed premenopausal women possessing the 7/7 TA repeat polymorphism had significantly reduced TC concentrations, versus individuals with the 6/7 or 6/6 polymorphism. The 7/7 TA repeat polymorphism is associated with hyperbilirubinemia [58], however, bilirubin concentrations were not reported in this study.…”
Section: Bilirubin and Lipid Status 141 Gilbert's Syndromementioning
confidence: 71%
“…39,40 In addition, a recent study confirmed that there was an association between the uridine 5'-diphospho-glucuronosyltransferase 1A1 and TC and LDL-C levels in women with different hormonal status. 41 Similarly, a negative correlation between TB and blood pressure was only found in women. 42 Further research is warranted to clarify the sex difference of the effects of bilirubin.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA was extracted from leukocytes by a standard salting out methodology. The fragment containing the chromosomal region of interest of the UGT1A1 gene was amplified by polymerase chain reaction (PCR), using the primers described by Smiderle et al 9 The size of the amplicons was determined by capillary electrophoresis on the ABI PRISM 310 Genetic Analyzer (Applied Biosystems, USA).…”
mentioning
confidence: 99%